Amphiphilic Surfactants and Amphiphilic Polymers: Principles of Molecular Assembly - Iborra, Agustin (2011)
The use of amphiphilic macrosurfactants as emulsifying agents has shown to have higher efficiency with respect to low molecular weight surfactants. Traditionally, block copolymers have been the first macromolecular systems used for this purpose. Due to the introduction of controlled polymerization techniques in the late nineties, the last decade showed an increase in the number of papers that report the preparation of macromolecules with complex architectures. In this mini-review, we report some advances in the preparation of amphiphilic macromolecules, with special emphasis in copolymers with complex architectures, star and cylindrical. We present a summary list about the synthetic methods and monomers employed to obtain amphiphilic systems as possible alternatives to traditional surfactant.